A review on clay‐reinforced ethylene propylene diene terpolymer composites. Issue 4 (1st February 2021) - Surya, Indra; Muniyadi, Mathialagan; Ismail, Hanafi
Abstract: In the new era of sustainable developments, various adaptations have been carried out in many industries to revolutionize the quest for sustainable materials as a method to reduce the dependency on petroleum feedstock. One of such inventions focusing on the automotive industries with new concepts of energy automotive such as electric and hybrid cars, as well as the utilization of inorganic materials as a components of polymer composites, which is expected to reduce the demand and utilization of various rubber composites in automotive parts. However, due to remarkable increment of service life and inherent properties, ethylene propylene diene terpolymer (EPDM) has showed the highest consumption in automotive segments and the fastest development rate in the field of polymer modification. Thus, a comprehensive review concerning the development of environmentally friendly EPDM‐based composites reinforced by various clay minerals is highlighted and presented in this article. The characteristic of EPDM, including the chemistry, processing, properties, and applications, as well as the current research on various types of rubber/clay composites, EPDM/clay composites, and rubber/bentonite (Bt) composites, is reviewed and reported. In addition, the characteristics, properties, and applications of different types of clay minerals such as layered silicates, Bt clays, and montmorillonites as reinforcement material in EPDM composites are also included. Finally, the drawbacks and challenges in developments of EPDM/clay composites and the existing improvizations through various compatibilization of EPDM/clay composite system such as chemical modification of clays, functionalization using coupling agents, and compatibilization through grafting are discussed by highlighting the important findings. Abstract : Structure of EPDM rubber with ethylidene norbornene as diene monomer and other dienes used in EPDM